Forecasting of Chinese primary energy consumption in 2021 with GRU artificial neural network - Liu, Bingchun; Fu, Chuanchuan; Bielefield, Arlene; Liu, Yan Quan (Energies, 2017)
The forecasting of energy consumption in China is a key requirement for achieving national energy security and energy planning. In this study, multi-variable linear regression (MLR) and support vector regression (SVR) were utilized with a gated recurrent unit (GRU) artificial neural network of Chinese energy to establish a forecasting model. The derived model was validated through four economic variables; the gross domestic product (GDP), population, imports, and exports. The performance of various forecasting models was assessed via MAPE and RMSE, and three scenarios were configured based on different sources of variable data. In predicting Chinese energy consumption from 2015 to 2021, results from the established GRU model of the highest predictive accuracy showed that Chinese energy consumption would be likely to fluctuate from 2954.04 Mtoe to 5618.67 Mtoe in 2021.
55 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000414578400008 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: China; Energy consumption; Energy planning; Energy security; Energy utilization; Forecasting; Forecasting modeling; Forecasting scenarios; Gated recurrent unit; Gross domestic products; Multi-variable linear regression; Multivariable systems; Neural networks; Primary energy consumption; Support vector regression (SVR); dept.ils; energy consumption; energy planning; forecasting scenarios; gated recurrent unit

Equitable access: Information seeking behavior, information needs, and necessary library accommodations for transgender patrons - Drake, Aubri A.; Bielefield, Arlene (Library & Information Science Research, 2017)
This study highlights the unique accommodations integral to welcoming transgender library patrons. Research shows transgender people have unique needs which differ from lesbian, gay, bisexual, and queer (LGBQ) individuals, and experience substantial barriers to obtaining quality library service. Most studies in the past exploring the needs of lesbian, gay, bisexual, and transgender library users focused exclusively on LGBQ users. This study surveyed adult transgender individuals (n = 102) with an online questionnaire. The majority of participants were white, designated female at birth, and under 40 years old. Survey respondents needed libraries to make accommodations for them to feel safe (p ¡ 0.001). The top 5 accommodations needed were recent transgender literature, gender identity or expression as part of library nondiscrimination policy, gender neutral, single-stall bathrooms where a key did not need to be requested, recent LGBQ literature), and an established remote process for name change.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000408303500002, lens.org/107-673-593-066-888 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: dept.ils